Style and influence of longfellow - Moore, Mae (My University, 1898)
Introduction: In 1807 a child was born in Portland, Maine, whose name at home and abroad was to become a household word. It can be truly said that no name is more familiar or more dearly loved where the English language is known than the name of Henry Wadsworth Longfellow. At the age of fourteen, Longfellow entered Bowdoin College, and graduated with honors in four years. After this, he studied for a time in the law office of his father, but he did not like this. He accepted a position to teach modern languages, and to prepare him more fully for this position, he went to Europe. In 1829, he came home and entered upon his duties. In 1835 his first great work “Outer Mer” was published, this at once was popular, and gained him an enviable fame. Soon after this, he received a call to the professorship of modern languages and literature in Harvard University. Again he went abroad to study source of the northern nations of Europe. He returned in the following year to his new positions, which he held until 1854, when he resigned to devote himself to his literary work.
Citation: Moore, Mae. Style and influence of longfellow. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: English Language; Europe; Professorship; Modern Languages; Theses; Manuscripts (documents)